2013
DOI: 10.1007/s11095-013-1031-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving Intracellular Doxorubicin Delivery Through Nanoliposomes Equipped with Selective Tumor Cell Membrane Permeabilizing Short-Chain Sphingolipids

Abstract: C₈-GluCer or C₈-GalCer incorporated in DoxNL selectively improved intracellular drug delivery upon transfer to tumor cell membranes by local enhancement of cell membrane permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Studies toward the mechanism described rapid SCS delivery from the liposomal to the tumor cell membrane independent of liposomal uptake, which preceded enhanced liposomal drug influx [14,21]. Previous studies demonstrated that C 8 -GluCer or C 8 -GalCer by themselves is innocuous to cells, as empty SCS-liposomes did not cause cell cytotoxicity [21]. In our formulations the antitumor activity is merely related to co-formulated drug (MTO).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Studies toward the mechanism described rapid SCS delivery from the liposomal to the tumor cell membrane independent of liposomal uptake, which preceded enhanced liposomal drug influx [14,21]. Previous studies demonstrated that C 8 -GluCer or C 8 -GalCer by themselves is innocuous to cells, as empty SCS-liposomes did not cause cell cytotoxicity [21]. In our formulations the antitumor activity is merely related to co-formulated drug (MTO).…”
Section: Discussionmentioning
confidence: 73%
“…SCS upon their insertion into cell membranes exerts drug transport enhancing properties to amphiphilic drugs such as Doxorubicin (Dox) and MTO [14,[19][20][21][22]33]. SCS preferentially exerts these properties toward tumor cell membranes, a phenomenon which is likely related to an aberrant makeup of these membranes in comparison with those of normal cells [14,21,22]. A tumor cell selectivity has been observed for the drug uptake enhancing effect of SCS [21,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations